2014
DOI: 10.1111/jorc.12088
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Services for Tourists to the Veneto Region: A Qualitative Study

Abstract: Tourist dialysis centres are necessary to make the right to freedom of movement for patients with ESKD a reality. The findings suggest that communicating and coordinating high-quality care across borders in the EU may be facilitated by increased standardisation of norms and documents for continuity of care, such as care plans and discharge summaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…8,16,17,36 Language barrier was identified as the most common barrier. 18,23,27 It has led to miscommunication and anxiety between patients and health care professionals. Research with 66 respondents (n = 47 patients and n = 19 health professionals) indicated that physicians and nurses were expected to speak more than 1 language due to limited interpreter availability.…”
Section: Motivators and Barriers For Medical Tourismmentioning
confidence: 99%
“…8,16,17,36 Language barrier was identified as the most common barrier. 18,23,27 It has led to miscommunication and anxiety between patients and health care professionals. Research with 66 respondents (n = 47 patients and n = 19 health professionals) indicated that physicians and nurses were expected to speak more than 1 language due to limited interpreter availability.…”
Section: Motivators and Barriers For Medical Tourismmentioning
confidence: 99%
“…19 Some other groups will be particularly affected, such as patients on dialysis who benefit from provisions that allow them to receive it in centres in other Member States. 20 It is also unclear what will happen to UK pensioners living in the EU27 who are in the middle of a course of treatment there and are no longer entitled to cover, who would be protected under the Withdrawal Agreement.…”
Section: Financingmentioning
confidence: 99%
“…Currently, there is no standardized process after an initial travel request is accepted by a destination dialysis unit, 11 leading to potential ineffective information transfer between the home unit and the transient dialysis unit. The heterogeneity of dialysis processes can be even more pronounced at some international travel sites 12 . Participants in our study reported that missing information delayed the processing of travel requests, which affected patient care at the receiving end.…”
Section: Discussionmentioning
confidence: 71%
“…The heterogeneity of dialysis processes can be even more pronounced at some international travel sites. 12 Participants in our study reported that missing information delayed the processing of travel requests, which affected patient care at the receiving end. Incorporating dialysis into the travel itinerary added a layer of complexity that patients must endure in exchange for the joy and leisure experience of travel.…”
Section: Discussionmentioning
confidence: 78%